Increased Expression of YAP Inhibited the Autophagy Level by Upregulating mTOR Signal in the Eutopic ESCs of Endometriosis - Pei, Tianjiao; Luo, Bin; Huang, Wei; Liu, Dong; Li, Yujing; Xiao, Li; Huang, Xin; Ouyang, Yunwei; Zhu, Huili (Frontiers in Endocrinology, 2022)
We first reported that the Hippo-YAP signaling pathway plays a critical role in the pathogenesis of endometriosis (EMS). Autophagy is also related to the invasion ability of endometrial cells and involves in the pathogenesis of EMS through multi-levels. But the precise regulatory mechanism of YAP on autophagy in the eutopic endometrial stromal cells (ESCs) is still unclear. Primary eutopic ESCs of EMS patients(n=12) and control patients without EMS (n=9) were isolated and cultured to investigate the expressions of YAP and mTOR, the role of YAP in autophagy and the effect of YAP-autophagy signal on the decidualization of the eutopic ESCs. Endometriosis-related sequencing data (GSE51981) in GEO database was used to find the genes significantly correlated with YAP. We found that 155 genes with significant differences in the interaction with YAP in EMS from the dataset, and autophagy pathway was significantly enriched. Following on from our previous studies of YAP knockdown, overexpression of YAP resulted in an increased expression of mTOR and decreased ratio of LC3-II/LC3-I, autophagy markers, in the eutopic ESCs, transmission electron microscope (TEM) observation also showed the fewer autophagosomes compared with the control cells. Furthermore, ESCs of Rapamycin-treated group showed significant decidual-like changes with significantly increased decidual prolactin level at 72h after in vitro decidualization. These results demonstrate that the increased YAP inhibited the level of autophagy by upregulating mTOR signal in the eutopic ESCs of endometriosis. YAP-autophagy signal plays an important role in the pathogenesis of endometriosis associated infertility.